3D printing of multimaterial gripper for tunable rigidity and shape conformance - Lim, Jian Yee (Nanyang Technological University, 2023)
In the field of 3D printing, soft robotics have made remarkable progress, yet certain applications face limitations due to constraints in fine control and gripping force. These limitations hinder their effectiveness in handling a wide range of objects and tasks, restricting their potential in various industrial and assistive applications.